Comparative analysis of the concepts of “law enforcement agencies” and “discretionary powers” in the international legal systems - O. A. Prysyazhnyuk (Law and Safety)
The article makes a comparative analysis of the concepts of “law enforcement agencies” and “discretionary powers” in the international legal systems on the example of the USA, the UK, Germany, France and Japan. The purpose of the study is to examine the legal acts that define the functioning of these concepts in each country, as well as to analyse in-depth the mechanisms of their implementation within the framework of legislative and practical activities of law enforcement agencies. An important part of the study is an assessment of how national legal systems interpret the powers of law enforcement agencies, including the police, prosecutors and other state institutions that contribute to law enforcement and security. Particular attention is paid to how these powers affect the efficiency and effectiveness of law enforcement, as well as the ability of law enforcement officers to make decisions in real, often unpredictable situations.